Experimental investigation on dynamic behaviour of bubbles emerging from micro‐capillary orifice in a flow channel. (14th November 2022) - Guo, Chenglong; Chai, Wang; Lyu, Qian; Min, Ming; Wang, Wei; Liang, Lin
Abstract: The flow phenomenon of liquid with bubbles is widespread in various industrial fields, which determines the mass transfer characteristics of the equipment. In this work, the dynamic behaviour of bubbles emerging from micro‐capillary orifice in a flow channel was studied by a visualization experiment, while the effects of gas flow rate and liquid flow rate on these processes of bubble growth, departure, and inrush were explored. The experimental results showed that one bubble formation cycle can be divided into three stages: Waiting, departure, and inrush, as well as the dynamic behaviour of bubble emerging from micro‐capillary orifice in a flow channel, were significantly affected by gas flow rate and liquid flow rate. At a higher gas flow rate, the growth time and the departure time were shorter, as well as the departure volume of the leading bubble and the inrush volume of the trailing bubble were smaller, while the transverse longitudinal ratio fluctuated more violently, and the swing amplitude of the bubble centroid was greater. With an increasing liquid flow rate, the growth time, the departure time, and the inrush time shortened, while the departure volume of the leading bubble decreased and the fluctuation of the bubble centroid weakened. These findings are conducive to improving the performance of the equipment by optimizing the design of the aerator to regulate the dynamic behaviour of bubbles.